2021
DOI: 10.1016/j.appdev.2021.101296
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the home music environment of children with various developmental profiles

Abstract: Families with young children with and without developmental disabilities often create a musically rich home environment. Parent-child music engagement, like singing play songs, is associated with positive outcomes for children, parents, and their relationship. However, little is known about if the home music environment differs across diagnostic groups and if parent-child music engagement relates to parent-child affective attachment across families of diagnostically diverse children. Using an online questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…Infant-directed singing captures infants’ attention ( 5 , 6 ), modulates infants’ arousal ( 5 , 7 9 ), and reduces infants’ distress ( 8 , 10 ) [even more so than infant-directed speech ( 8 , 10 )]. For caregivers, singing to infants regulates their own arousal levels ( 9 , 11 ) and increases their perceived affective connection to their infants ( 11 13 ).…”
mentioning
confidence: 99%
“…Infant-directed singing captures infants’ attention ( 5 , 6 ), modulates infants’ arousal ( 5 , 7 9 ), and reduces infants’ distress ( 8 , 10 ) [even more so than infant-directed speech ( 8 , 10 )]. For caregivers, singing to infants regulates their own arousal levels ( 9 , 11 ) and increases their perceived affective connection to their infants ( 11 13 ).…”
mentioning
confidence: 99%
“…Parents also expressed interest in shared parent–child activities. As musical activities are a common form of positive social interaction between parents and children and children and their peers, 21,49 integrated music classes provide a context aligned with parents’ goals for community participation. Parents typically seek out recreational community activities that are enjoyable, aligned with children's interests, and meaningful for families 50 .…”
Section: Discussionmentioning
confidence: 99%
“…21,[33][34][35] Joint music activities also support social connection and bonding, 36,37 including between parents and their children, and between unfamiliar adults or children. 21,33,38,39 While both group and individual singing are associated with decreases in the production of the stress-related hormone cortisol, only group singing is associated with increases in oxytocin, a neuropeptide associated with social bonding. 37 Joint music activities impact social connection in part by increasing interpersonal synchrony, which occurs due to music's predictable melodic and rhythmic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The families would sometimes mention singing to their child as well. The primary means of musical engagement at home echoed the findings of Steinberg, Shivers, et al (2021), who indicated that children with learning support needs engage in seven main musical activities at home. These are singing, playing instruments, playing with musical toys, listening to recorded music, watching music videos, dancing to music and engaging in music activities with another person.…”
Section: Introductionmentioning
confidence: 64%
“…The caregivers have positive experiences with their children and these experiences lead the carers to see and interact with their children differently (Kaenampornpan, 2015(Kaenampornpan, , 2017. This work with younger children often happens in home settings, therefore music therapists learn about the home environment (Steinberg, Shivers, et al, 2021). Music therapists are aware that being allowed into a child's home and the family's private lives is an honour and it allows them to get to know the family on a more intimate level (Mitchell, 2017).…”
Section: Music Therapy With Families Of Children With Learning Suppor...mentioning
confidence: 99%